Comprehensive Parametric Study of Blockage Effect on the Performance of Horizontal Axis Hydrokinetic Turbines - Abdulaziz Abutunis; Venkata Gireesh Menta (Energies, 2022)
When a hydrokinetic turbine operates in a confined flow, blockage effects are introduced, altering the flow at and downstream of the rotor. Blockage effects have a significant effect on the loading and performance of turbines. As a result, understanding them is critical for hydrokinetic turbine design and performance prediction. The current study examines the main and interaction effects of solidity (σ), tip speed ratio (TSR), blockage ratio (ε), and pitch angle (θ) on how the blockage influences the performance (CP) of a three-bladed, untwisted, untapered horizontal axis hydrokinetic turbine. The investigation is based on validated 3D computational fluid dynamics (CFD), design of experiments (DOE), and the analysis of variance (ANOVA) approaches. A total number of 36 CFD models were developed and meshed. A total of 108 CFD cases were performed as part of the analysis. Results indicated that the effect of varying θ was only noticeable at the high TSR. Additionally, the rate of increment of CP with respect to ε was found proportional to both TSR and <semantics>σ</semantics>. The power and thrust coefficients were affected the most by <semantics>σ</semantics>, followed by ε, TSR, and then θ.